PEGylated Recombinant Human Growth Hormone Jintrolong® Exhibits Good Long-Term Safety in Cynomolgus Monkeys and Human Pediatric Growth Hormone Deficiency Patients - Wei Wu; Juan Zhou; Chuandong Wu; Qian Zhou; Xiaoyu Li; Yanlin Zhang; Conglin Zuo; Jun Yin; Ling Hou; Shuyang Wang; Hongyang Gao; Tianhong Luo; et al. (Frontiers in Endocrinology, 2022)
Jintrolong® is a long-acting PEGylated recombinant human growth hormone (PEG-rhGH) developed for weekly injection in patients with pediatric growth hormone deficiency (PGHD). Although PEG modification of therapeutic proteins is generally considered safe, concerns persist about the potential for adverse vacuolation in tissues with long-term exposure to PEG-included therapies, particularly in children. We assessed the safety of Jintrolong® in cynomolgus monkeys with an examination of vacuolation in the brain choroid plexus (CP) and reported long-term clinical safety data obtained from children with PGHD. The toxicity of Jintrolong® was assessed following the 52-week administration with doses at 0.3, 1, or 3 mg/kg/week. The levels of vacuolation of CP in animals were dose-dependent and at least partially reversible after a 104- or 157-week recovery period. Vacuolation in the CP epithelium did not lead to obvious subcellular structural or cell functional abnormalities. Compared with the clinical dose of 0.2 mg/kg/week Jintrolong® in PGHD patients, exposure in monkeys under NOAEL 3 mg/kg/week exhibited safety margins greater than 120.5, the predicted minimum dose to induce vacuolation in monkeys is equivalent to 1.29 mg/kg/week in humans, which is 6.45-fold higher than the clinical dose. The safety data acquired in clinical trials for Jintrolong® were also analyzed, which included phase III (360 patients), phase IV (3,000 patients) of 26-week treatment, and a follow-up study with treatment lasting for 3 years. There was no statistically significant difference in the incidence of adverse reactions between the Jintrolong® group and the daily rhGH control group (no PEG), and no new adverse effects (AE) were observed in the Jintrolong® group at the clinical therapeutic dose of 0.2 mg/kg/week.